Effect of a constant rate infusion of remifentanil hydrochloride on left ventricular systolic and diastolic function in propofol-anesthetized dogs - Marques, Marcel G. [UNESP]; Cancelli, Carlos H. B. [UNESP]; Fernandes, Carollina M. S. [UNESP]; Games, Bruna M. M. [UNESP]; Floriano, Beatriz P. [UNESP]; Perri, Silvia H. V. [UNESP]; Sousa, Marlos G. [UNESP]; Ferreira, Wagner L. [UNESP]; Santos, Paulo S. P. [UNESP] (Amer Veterinary Medical Assoc, 2018)
OBJECTIVE To assess the effects of a constant rate infusion (CRI) of remifentanil hydrochloride on left ventricular systolic and diastolic function in healthy propofol-anesthetized dogs. ANIMALS 6 healthy Beagles. PROCEDURES Each dog underwent 2 experimental treatments separated by a 7-day interval. In 1 treatment, anesthesia was induced with propofol and maintained with a CRI of propofol (0.6 mg/kg/min); dogs also received a CRI of saline (0.9% NaCl) solution. In the other treatment, anesthesia was similarly induced and maintained with propofol; dogs also received a CRI of remifentanil (0.3 mu g/kg/min). Doppler echocardiographic and hemodynamic variables of interest were determined at baseline (before anesthesia) and at 20, 40, and 60 minutes following the simultaneous start of the 2 CRIs of each treatment; all CRIs were administrated for 60 minutes. RESULTS For the 2 treatments, end-diastolic and end-systolic volume indices did not differ from baseline or at any time point. Peak tissue Doppler-derived mitral annulus systolic velocity decreased from baseline with both treatments; however, no differences were found between treatments at any time point. Mean arterial blood pressure decreased similarly with both treatments. Heart rate and Doppler-determined cardiac index decreased significantly with the propofol-remifentanil treatment, compared with findings for the propofol-saline solution treatment. For the propofol-remifentanil treatment, the ratio of peak velocity flow in early diastole to that in late diastole remained > 1.80, whereas the ratio of early to late Doppler-derived mitral annulus velocity had a normal relaxation pattern. CONCLUSIONS AND CLINICAL RELEVANCE Results of this study indicated that a CRI of remifentanil administered along with a CRI of propofol does not impair left ventricular systolic and diastolic function in healthy dogs.